Systematic substrate identification indicates a central role for the metalloprotease ADAM10 in axon targeting and synapse function - Kuhn, Peer-Hendrik; Colombo, Alessio Vittorio; Schusser, Benjamin; Yildiz, Daniela; Wetzel, Sebastian; Schepers, Ute; Herber, Julia; Ludwig, Andreas; Kremmer, Elisabeth; Montag, Dirk; Müller, Ulrike C.; Schweizer, Michaela; et al. (eLife, 2016)
Metzincin metalloproteases have major roles in intercellular communication by modulating the function of membrane proteins. One of the proteases is the a-disintegrin-and-metalloprotease 10 (ADAM10) which acts as alpha-secretase of the Alzheimer's disease amyloid precursor protein. ADAM10 is also required for neuronal network functions in murine brain, but neuronal ADAM10 substrates are only partly known. With a proteomic analysis of Adam10-deficient neurons we identified 91, mostly novel ADAM10 substrate candidates, making ADAM10 a major protease for membrane proteins in the nervous system. Several novel substrates, including the neuronal cell adhesion protein NrCAM, are involved in brain development. Indeed, we detected mistargeted axons in the olfactory bulb of conditional ADAM10-/- mice, which correlate with reduced cleavage of NrCAM, NCAM and other ADAM10 substrates. In summary, the novel ADAM10 substrates provide a molecular basis for neuronal network dysfunctions in conditional ADAM10-/- mice and demonstrate a fundamental function of ADAM10 in the brain.
Gesehen am 03.06.2020